KARAKTERISTIK PENDERITA MIOMA UTERI YANG DI RAWAT INAP DI RSUD DR. PIRNGADI MEDAN TAHUN 2009-2011 - Linda Yana Ginting (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2012)
Uterine myoma is a benign tumor come from the muscle of uterus and connective tissue on it. Proportion uterine myoma in Indonesia 2,39-11,7% from all hospitalized benign gynecology. In Pirngadi General Hospital was found 152 cases of uterine myoma during 2009-2011. To know the characteristics of uterine myoma patients who are hospitalized in Pirngadi General Hospital Medan has been done by using case series design. Data was analyzed by using test of chi-square, kruskal wallis and t-test. Proportion based on sosiodemography, highest age 40-49 years old 59,9%, Batak ethnic 57,9%, Islamic 59,2%, senior high school 72,4%, housewife 69,1%, marriage 91,4%, lives in Medan 65,8%. Multipara parity 45,2%, Intramural myoma 41,9%, the size of myoma 5-10 cm 67,5%, abnormal bleeding 51,4%, not using of contraception 69,8%, menarche 90,8%, hysterectomy 50,0%, total abdominal hysterectomy 76,3%, average length of stay 7,20 days, discharged under medical treatment 90,1%. There is significant differences between age patient and medical therapy (p=0,000). The average length of uterine myoma patients who care conservatively shorter than with myomectomy and hysterectomy (p=0,000). The average length of uterine myoma patients when discharged by her own request shorter than under medical treatment (p=0,000). Pirngadi General Hospital suggested to complete the medical record especially for parity, location of myoma, size of myoma, using of contraception, surgery indication, weight, high of patients. For woman who has abnormal bleeding to check herself soon whether she has the tendency of getting the uterine myoma. Key words : Uterine myomas, characterictics of patients, Pirngadi General Hospital Medan